Spatial Variation in Mercury Bioaccumulation and Magnification in a Temperate Estuarine Food Web - Fonseca, Vanessa F.; França, Susana; Duarte, Bernardo; Caçador, Isabel; Cabral, Henrique N.; Mieiro, Cláudia L; Coelho, João P.; Pereira, Eduarda; Reis-Santos, Patrick (Frontiers in Marine Science, 2019)
Estuaries are renown sinks or repositories of contaminants and reflect historical pollution of persistent compounds. In particular, mercury (Hg) contamination is widespread in coastal environments and occurs in both inorganic (THg) and highly toxic organic forms (OHg) with high bioaccumulation potential. Trophic magnification factors have been increasingly used to quantify biomagnification and represent the average rate of change in contaminant concentration throughout a food web. Here, we assessed small-scale spatial variation in THg and OHg concentrations, as well as variations in local trophic magnification factors in three segregated areas of the Tejo estuary. Selected sites covered a gradient of contamination from industrial Hg hotspots to a natural reserve area, and are key nursery areas for multiple fishes. We analyzed concentrations in sediment and biota, representing the entire local food webs. Samples included sediments, primary producers (salt marsh plants), primary consumers (macrobenthic invertebrates) and top consumers (fish muscle and liver), and the trophic web structure was characterized via SIAR mixed-modeling of nitrogen and carbon isotopic ratios. Spatial variation in Hg concentrations was observed in sediment and biota (but not for all species), with highest concentrations in the area near historical mercury input. Hg concentrations increased with trophic level, and so did the OHg fraction (% of OHg relative to THg), with mean maximum values up to 48.7% and 94.9% in invertebrates and fish, respectively. Trophic magnification factors were positive for all sites (p<0.05 for all regressions), ranging between 1.56 to 1.76 and 1.78 to 2.47 for THg and OHg, respectively. Overall, rates of mercury bioaccumulation were similar across sites with variations in biota´s Hg concentrations reflecting baseline differences in site environmental levels. Understanding mercury bioaccumulation and magnification in estuarine biota is critical to safeguard the multiple ecologic functions and economic benefits estuaries provide.